SUPERVISI KLINIS DAN PENILAIAN BERBASIS KELAS - Rahmadani (WIDYABORNEO, 2020)
Based on the preliminary study results from the supervision of the class, the teachers of Islamic Education (PAI) conduct the teaching and learning activities without preparation. In addition, they also have not made the preparation of a complete class assessment such as making of Minimum Mastery Level (KKM), assessment guide, assessment analysis, and they do not distribute the result assessment immediately to the students which it is important to do by the teachers in Class Based Assessment. In relation to these matters, it is necessary to conduct fostering-guidance through clinical supervision. This study aims to improve the ability of Islamic Education (PAI) teachers in conducting Class-Based Assessment through clinical supervision at SDN Tambalangan, Centre Amuntai District, Hulu Sungai Utara Regency Kalimantan Selatan provice. This study is a School Action Research that involving of 3 (three) existing PAI teachers. The study was conducted with two Cycles. The indicator of successis: teachers are successful in conducting classroom assessments when they will meet the criteria of getting a score of more than or equal to 77.8 (good category). From the analysis result, it is found that there is an improvement in the quality of teacher assessment implementation from Cycle I (score 67) with enough categories to Cycle II (score 80) with good category. Thus it can be concluded that through the optimization of clinical supervision can improve the ability of PAI teachers in carrying out Class-Based Assessment at SDN Tambalangan, Centre Amuntai District, Hulu Sungai Utara Regency Kalimantan Selatan provice.